2022
DOI: 10.1101/2022.10.07.511173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tuning of cytokine signaling through imbalanced abundances of receptors and kinases

Abstract: Cells rely on cytokines to coordinate their activation, differentiation, proliferation and survival. In particular, γC cytokines (interleukins IL-2, 4, 7, 9, 15, and 21) regulate the fate of leukocytes. The signaling cascade induced by these cytokines is relatively simple, and involves the phosphorylation of receptor-associated Janus-like kinases (JAK). Here, we explore the cell-to-cell variability of cytokine responses in primary mouse T~cells, and find a paradoxical and quantitative imprint of receptor exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been shown that overexpression of cell surface receptors can decrease the cellular response to their cognate biological stimuli [ 45 ], and that overexpression of a receptor subunit without concordant overexpression of downstream signaling molecules can lead to the formation of receptor complexes capable of binding ligands but unable to transduce signals [ 46 ]. As FLAG-Iso1 overexpression augmented the IFNL3 response, regardless of dox-induction, we find it less likely that FLAG-Iso2 overexpression diminished cell sensitivity to IFNL3 by titrating necessary signaling components.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that overexpression of cell surface receptors can decrease the cellular response to their cognate biological stimuli [ 45 ], and that overexpression of a receptor subunit without concordant overexpression of downstream signaling molecules can lead to the formation of receptor complexes capable of binding ligands but unable to transduce signals [ 46 ]. As FLAG-Iso1 overexpression augmented the IFNL3 response, regardless of dox-induction, we find it less likely that FLAG-Iso2 overexpression diminished cell sensitivity to IFNL3 by titrating necessary signaling components.…”
Section: Discussionmentioning
confidence: 99%